PENGGUNAAN INTERNET OLEH MAHASISWA FISIP UNDIP - Djoko Setyabudi, Joyo Nur Suryanto Gono, (JURNAL ILMU SOSIAL, 2013)
This study explored the usage of internet for study enrichment and pleasure. Understanding online media audience was becoming increasingly important in Social and Political Faculty, because internet access was one of the academic source used by the student. Most of students did not have sufficient knowledge for self information filtering to provide realible materials from internet and various online sources that fulfilled the academic and scientific requirement. Small number of student explored some opportunities for getting academicÂ  sources through internet, but unfortunately most of them did not have througly understanding to difer valid and reliable information for completing their academic tasks and research.